Efficient name matching based on a fast two-dimensional filter in named data networking. Issue 2 (4th March 2019) - Shubbar, Roaa; Ahmadi, Mahmood
ABSTRACT: Named data networking (NDN) is a recently proposed networking paradigm that aims to overcome the limitations of the Internet Protocol, while preserving its strengths by using named data rather than named hosts for communication. In NDN, the content is determined by its name, and each NDN packet has a name that determines the content it is bringing or forwarding. In this new paradigm, content names have a hierarchical structure and variable length and, therefore, these features will introduce new challenges to satisfy reasonable speed at large scale. In this paper we propose, design and implement a new approach called fast two-dimensional filter with hash table (FTDF-HT). In the proposed approach, a hash table storing the name prefixes, in a hierarchical manner, is only accessed when the proposed filter (FTDF) states that the name under querying exists. Thus, reducing the unnecessary access to the hash table. Moreover, the access to the hash table will be done with same hash function that is used for FTDF and this will minimize the search time. Our evaluation results show that FTDF-HT can achieve high lookup speed and exhibit good scalability to large-scale prefixes table.